Understanding research with children and young people - Clark, Alison; Flewitt, Rosie; Hammersley, Martyn; Robb, Martin (Sage, 2014)
How do views about children shape research concerned with their lives? What different forms can research with children take? What ethical issues does it involve? How does it impact on policy and practice, and on the lives of children themselves? This book helps you to understand how research is designed and carried out to explore questions about the lives of children and young people. It tackles the methodological, practical and ethical challenges involved, and features examples of actual research that illustrate: Different strategies for carrying out research ; Common challenges that arise in the research process ; Varying modes of engagement that researchers can adopt with participants and audiences and The impact that research can have on future studies, policy and practice.